On the error of the estimate of the spectral function of a stationary process - Bentkus, R. (Lithuanian Mathematical Journal, 1972)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Р. Бенткус. Об ошибке оценки спектральной функции стационарного процессаR. Bentkus. Apie stacionaraus proceso spektrinės funkcijos įvertinimo paklaidą